Exploring the Zt3LysM effector in Zymoseptoria tritici, a fungal phytopathogen of wheat - Steel, Luca (2024)
Fungal plant pathogens are a threat to food security, destroying enough crops annually to feed over 8% of the world’s rapidly growing population. Zymoseptoria tritici, a filamentous ascomycete, is responsible for Septoria Leaf Blotch disease on wheat. This devastating disease is associated with huge financial costs and yield losses. Current management strategies such as partially resistant wheat cultivars and fungicides do not provide sufficient control of this pathogen, and new strategies are urgently needed.